Surface seawater concentration data collected from the West Antarctic Peninsula during the Icebergs 3 JR19002 cruise in January 2020 ... - Jones, Rhiannon L.; Annett, Amber L.; Sherrell, Robert; Flanagan, Oliver; Woodward, Malcolm; Meredith, Michael; Scourse, James D.; Lohan, Maeve (NERC EDS UK Polar Data Centre, 2025)
During the JR19002 Icebergs 3 cruise, samples from the surface seawater were collected from Zodiacs. Samples were collected with the motivation of determining the impact of retreating glaciers upon the surface ocean, such as the hydrography and biogeochemical composition of the surface ocean. Three main sites were visited during JR19002 from south to north: Marian Cove, Maxwell Bay, King George Island; Borgen Bay, Anvers Island; and Sheldon Cove, Ryder Bay, Adelaide Island. Small boat traversed each bay, collecting particulate and dissolved seawater samples. Parameters collected and determined include: stable oxygen isotopes, salinity, dissolved macronutrients, dissolved and particulate metals, radium and thorium activity. Funding: NERC grants, NE/P017630/1 (Dr Amber Annett) and NE/P003060/1 (Professor David Barnes). ... : Surface seawater for particulate and dissolved metals, radium, dissolved micronutrients, salinity, and stable oxygen isotopes were collected by hand using zodiac boats during the JR19002 Icebergs 3 cruise. Acid-cleaned bottles were rinsed and filled with surface seawater over the bow to avoid contamination from the Zodiac. Bottles were immediately capped and returned to the ship and processed. For total particulate digest, 4 L of seawater was pressure filtered onto 25mm Supor (PES) filters (0.45 µm pore size) and frozen immediately. filters were frozen immediately at -20 degrees C. Dissolved phase samples were filtered using a 0.2 micrometers Acropak cartridge filter and peristaltic pump and collected into acid-washed 125mL HDPE bottles (dissolved metals). All sampling and handling was performed according to GEOTRACES protocols. Three PES filters per site were subject to complete acid digestion using 10 percent HF/50 percent HNO3 (UpA, distilled) at 135 degrees C for 4 h following GEOTRACES protocol. ...